Synthesis, structural, thermal and dielectric properties of graphene oxide based barium titinate composite films: Possible materials for embedded capacitors. (December 2017) - Sohail, M.; Khan, M. Saleem; Saeed, Noor; Arif, M.; Irfan, M.; Omer, M.
Graphical abstract: Abstract: Graphene oxide (GO) based Barium titinate (BaTiO3 ) biphasic composite films were prepared by applying in-situ modified Hummer and ex-situ one pot blending techniques. Fourier transform infrared (FT-IR) and Ultraviolet-visible (UV–vis) spectroscopy confirmed the synthesis and composite formation of GO and GO-BaTiO3 composites. Glass transition (Tg ) and crystallization temperature (Tc) values were obtained from TGA. X-ray diffraction was performed for a preliminary phase and structural analysis. Extensive dielectric and conductivity data was analyzed in the frequency range from 1 MHz to 3 GHz at ambient temperature. The results suggest the suitability of the prepared materials for applications in embedded capacitors.